Interpreting conflict mediation in Kosovo and Macedonia - Todorova, Marija (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
While the basic role of interpreters is to facilitate communication, situations of conflict mediation and third party intervention very often surpass the usual role and skills needed by interpreters in any other situations. Interpreters in conflict mediation need to be more sensitive to the background situation, emotions, and need to be able to sense perceptions and feelings. They also need to help the mediator create trust, open communication channels, and understand cultural differences and emotions. Drawing on Touval’s (2002) influential argument that biased mediators in international disputes are often the most effective, as well as Kriesberg’s (1991) concept of the quasi-mediator, this paper looks at the role of interpreters in conflict mediation, with a particular focus on the issue of their prescribed or perceived neutrality, based on a survey of interpreters and mediators involved in conflict mediation processes in Kosovo and Macedonia. The concept of neutrality is revisited in terms of conflict mediation theory as well as interpreting theory. Recommendations are provided for training in mediation for interpreters.